Penerapan Metode Sensori Motor untuk Meningkatkan Kemampuan Artikulasi pada Anak dengan Disabilitas Intelektual: Studi Kasus Tunggal - Hikmatun Sadiah; Sarah Arif; Sekar Ayu; Zakkiyah Putri (Politeknik Arutala Johana Hendarto [d.h. Akademi Terapi Wicara], 2023)
Several studies have shown that speech sound disorders in children with intellectual disabilities impact communication with their environment. They have more difficulty with expressive language and speech intelligibility than receptive. Interventions are needed to improve speech skills, especially in articulation skills.